"Shudder" and the Aesthetics and Platform Logics of Genre-Specific SVOD services. (February 2023) - Balanzategui, Jessica; Lynch, Andrew
Major subscription-video-on-demand (SVOD) services including Netflix and Apple TV+ target a wide range of consumers through catalogs that house a diverse variety of genres. However, as the SVOD ecology has evolved, services have emerged that focus on particular genres, and thus target enthusiasts of specific content types. This article examines the horror-focused SVOD service "Shudder" to highlight how these genre-specific SVOD services curate content in ways that differ from major services like Netflix. Unlike the top-tier generalist SVODs, niche services like Shudder do not appeal to users via personalized algorithmic recommendation of titles from a seemingly limitless catalog: instead, these services are branded around the affective pleasures of and fan cultures surrounding specific genres. Our analysis of Shudder combines interface and genre analysis to illuminate how the platform offers a "phenomenal experience" of generic immersion in ways that reflect on new intersections between SVOD platforms, genre, nostalgia, and cinephilic subcultures.